PENDAMPINGAN PENGOLAHAN SAMPAH ORGANIK DALAM UPAYA MENCAPAI SDG ZERO HUNGER DI DESA CILEUNYI KULON KABUPATEN BANDUNG - Dina Yulianti; Arry Bainus; Deasy Silvya Sari; Savitri Aditiany (Jurnal Abditani, 2023)
Sustainable Development Goals (SDGs) number 2 is "zero hunger," among the targets mentioned in the SDGs document are stunting prevention and sustainable agriculture. One of the causes of stunting is the lack of nutrition, especially foods that contain iron and zinc, which come from green vegetables. The community service carried out by the Team of the International Relations Study Program at Padjadjaran University integrates these targets by encouraging the village residents to process organic waste as fertilizer and grow vegetables organically. The community service carried out in the RW 22 Cileunyi Kulon Village in the form of assistance and consultation for the village residents so that they are consistent in processing organic waste and growing vegetables that are sources of iron and zinc. In this activity, the team conducted interviews and dialogue with the village residents (who had previously received education on processing organic waste and tools for organic farming) to evaluate their activities so far. Thus, the method used is PRA (Participatory Rural Appraisal), in which the team acts as a facilitator, and residents carry out the activities independently. The findings from this assistance are that consistent residents have strong motivation regarding the benefits of processing organic waste and growing organic vegetables.